Performance evaluation of Laser-Induced Screen Printed Electrodes for electrochemical detection - Badrol Hisham, Balqis Nurnadia; Md Ralib @ Md Raghib, Aliza 'Aini; Nordin, Anis Nurashikin; Tung, Lun Hao; Ab Rahim, Rosminazuin; Mohd Zain, Zainiharyati (IEEE, 2023)
Screen printing is a well-known technique for producing disposable and low-cost screen-printed carbon electrode (SPCE) sensor. SPCE sensors have been used in many applications such as disease detection, toxin detection, disease monitoring for the environment, and food analysis. Despite its outstanding advantages, electrochemical-based SPCE sensors have relatively low sensitivity as compared to chromatography-based and fluorimetry-based conventional sensors. A modification by improving the electrode’s materials may be implemented to produce an effective and sensitive SPCE sensor. Thus, in this study, a comparison of material between laser-induced graphene screen-printed electrode (LIG-SPE) and currently existing and widely used screen-printed carbon electrode (SPCE) is presented. Cyclic Voltammetry (CV) was conducted to compare the performance of the fabricated sensors for electrochemical detection and the R² calibration curves were performed to determine the linearity. The results shows that LIG SPE has better linearity (R² is 0.9596) compared to SPCE.